2006
DOI: 10.1016/j.str.2005.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Catalysis of the Di-Heme Cytochrome c Peroxidase from Paracoccus pantotrophus

Abstract: Bacterial cytochrome c peroxidases contain an electron transferring (E) heme domain and a peroxidatic (P) heme domain. All but one of these enzymes are isolated in an inactive oxidized state and require reduction of the E heme by a small redox donor protein in order to activate the P heme. Here we present the structures of the inactive oxidized and active mixed valence enzyme from Paracoccus pantotrophus. Chain flexibility in the former, as expressed by the crystallographic temperature factors, is strikingly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
110
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(122 citation statements)
references
References 43 publications
11
110
0
1
Order By: Relevance
“…The crystal structure of P. pantotrophus CCP was obtained in two different redox states, a fully oxidised form and a mixed-valence form, which supports these observations [11]. The comparison of these two structures revealed that the inactive form presents a closed conformation where the peroxidatic haem adopts a hexacoordinate structure, hindering the peroxidatic reaction from taking place.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…The crystal structure of P. pantotrophus CCP was obtained in two different redox states, a fully oxidised form and a mixed-valence form, which supports these observations [11]. The comparison of these two structures revealed that the inactive form presents a closed conformation where the peroxidatic haem adopts a hexacoordinate structure, hindering the peroxidatic reaction from taking place.…”
Section: Introductionsupporting
confidence: 70%
“…The comparison of these two structures revealed that the inactive form presents a closed conformation where the peroxidatic haem adopts a hexacoordinate structure, hindering the peroxidatic reaction from taking place. The active mixed-valence form shows conformational changes in four different loop regions and the peroxidatic haem becomes pentacoordinate, providing access of the substrate to the active site [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In another example, reduction of the haem iron by synchrotron radiation followed by transient warming to room temperature was used to generate and trap intermediate states in crystalline myoglobin (Hersleth et al, 2008). Research on other crystalline redox-sensitive proteins for which X-rayinduced reduction has been reported at temperatures close to 100 K (Berglund et al, 2002;Adam et al, 2004;Baxter et al, 2004;Mees et al, 2004;Roberts et al, 2005;Echalier et al, 2006;Beitlich et al, 2007;Kuhnel et al, 2007;Pearson et al, 2007;Hough et al, 2008) could benefit from temperaturecontrolled crystallography if structural information on intermediate states were of interest.…”
Section: Temperature-controlled Kinetic Cryocrystallography To Characmentioning
confidence: 99%
“…Therefore, in the presence of calcium ions, and coupled to the reduction of the electron-transfer heme, a conformational change occurs in the polypeptide chain, mainly around the peroxidatic heme [18]. The peroxidatic heme loses one of the histidine axial ligands and becomes pentacoordinated and ready to react with the substrate [18,19].…”
Section: Nitrite Reductasementioning
confidence: 99%
“…The peroxidatic heme loses one of the histidine axial ligands and becomes pentacoordinated and ready to react with the substrate [18,19]. In the absence of calcium, the reduction of the electrontransfer heme does not promote the conversion of the peroxidatic heme into the pentacoordinated form, and the enzyme remains inactive.…”
Section: Nitrite Reductasementioning
confidence: 99%